Thermodynamic investigations for combustion-assisted synthesis of lithium orthosilicate powders - Benzeşik, Kağan; Yücel, Onuralp (Springer, 2024)
The study investigates the combustion-assisted synthesis of lithium orthosilicate (Li4SiO4) powders for potential CO2 capture applications. Technical-grade lithium carbonate and metallic silicon powders were used as starting materials. Synthesis conditions were explored across temperatures ranging from 500 to 900 °C and different holding durations. Thermodynamic modeling using FactSage 8.2 software suggested that Li4SiO4 production is feasible at temperatures of 700 °C and higher with metallic silicon as the silicon source, which was confirmed experimentally. Characterization of the synthesized powders involved X-ray diffraction, specific surface area determination, particle size distribution analysis, scanning electron microscopy, and CO2 uptake tests. Despite having the lowest Li4SiO4 content as 83.7%, the sample synthesized at 700 °C with 45 min of holding time showed the best CO2 uptake performance as 12.80 wt% while having the lowest crystallite size value (126.58 nm), the highest specific surface area value (4.975 m2/g) and the lowest average particle size value (10.85 µm) which are highly effective on the CO2 uptake performance of such solid sorbents. The study concludes that while challenges remain in achieving optimal CO2 capture performance, it lays a foundation for utilizing lithium orthosilicate in carbon capture applications.
Keywords: combustion synthesis; lithium orthosilicate; ceramic sorbent; CO2 capture; CO2